1981
DOI: 10.4327/jsnfs1949.34.4_287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potato Starch Granules on Digestive Enzymes of Rats

Abstract: The influences of potato starch-granules and cellulose on the digestive enzyme activities of adult and young rats were studied for various duration. When rats of 8 weeks old were fed on the diet than that of rats (control) fed a pregelatinized potato starch diet (PPS diet), and pancreatic protease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In vitro and in vivo experimental studies suggest that banana starch granules are largely indigestible [2][3][4]. Since the starch is poorly digestible and decreases as the banana ripens, and since the sucrose, fructose and glucose contents, which comprise the readily absorbable portion, increase with ripening, we wished to determine if compositional changes affect the plasma glucose and insulin response to ingestion of a defined amount of banana.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo experimental studies suggest that banana starch granules are largely indigestible [2][3][4]. Since the starch is poorly digestible and decreases as the banana ripens, and since the sucrose, fructose and glucose contents, which comprise the readily absorbable portion, increase with ripening, we wished to determine if compositional changes affect the plasma glucose and insulin response to ingestion of a defined amount of banana.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the influence of hardly digestive starch such as PSG on digestive tracts and enzymes of rats , and showed that a-amylase [EC 3.2.1.1.] activity in pancreas was significantly decreased by feeding rats on a PSG diet and that intestinal sucrase [EC 3.2.1 .48] activity was significantly increased, but that intestinal maltase [EC 3.2.1.20] and isomaltase [EC 3 .2.1.10] activities scarcely changed (4)(5)(6). These changes were also observed when feeding rats on a diet containing dietary fiber of high water-holding capacity, for example Konbu, a kind of sea vegetable (7).…”
mentioning
confidence: 99%